Engineering the civil engineering education: A capstone case study in a Malaysian university - Wan Abdullah Zawawi, N.A. (2013)
A Capstone course was introduced to a batch of graduating students in January 2011, aimed to strengthen the co-curriculum of a Civil Engineering degree programme. Comparison is made on the performance of three different batches of students. This paper highlights the improvement in grade distributions outcomes of a comprehensive engineering test introduced to the second and third batches. It is widely indicated that such all-inclusive assessment could positively impact the graduating students professionally. This is indeed an exciting development in engineering education as Capstone is not a familiar feature for Malaysian universities. Â© 2013 IEEE.